Food Waste Management Feasibility Study in Hotel X - Albana, Muhammad Hasan; Handayati, Yuanita (Journal of Business and Management, 2020)
Abstract. This paper aims to find out the problems that faced by 1000Kebun and help them in implementing food waste management for the Hotel X. Hotel X is a 5 star hotel located in Bandung, Indonesia with good reputation and experience in hotel industry. Most of Hotel X wastes are food waste and several Hotel X staffs realized that they have to conduct food waste management to have their own waste management system. However, they have zero experience in waste management, therefore they will conduct cooperation with 1000Kebun, one of organic community in Bandung. Since this will be the first time for 1000Kebun to implement food waste management, they faced several problems in structuring the business, detailing the food waste management process, and calculating the worth of investment for implementing food waste management. The results from this paper are the detailed business process of Hotel X using Business Process Modelling Notation (BPMN), cost benefit analysis using Net Present Value and Payback Period, and Hotel X food waste management business model canvas.Keywords: Business Process, Business Model Canvas, Business Process Modelling Notation, Cost Benefit Analysis, Food Waste Management.